Pengaruh Perilaku Impulsif Terhadap Kecenderungan Nomophobia Mahasiswa - Yuliana Nata; Fredericksen Victoranto Amseke (Majalah Ilmiah METHODA, 2024)
Nomophobia or no mobile phone phobia is a person's excessive fear of being away from gadgets. One of the influencing factors is nomophobia, which is impulsive behavior. This study aims to examine the influence of impulsive behavior on nomophobic tendencies of students in the pastoral counseling study program at the Kupang State Christian Institute. This research uses quantitative methods. Data collection tools used an impulsive behavior scale using the Impulsiveness Scale Version 11 (BIS-11) and a nomophobia scale using the Nomophobia Questionnaire (NMP-Q). The respondents in this study were 89 students in the pastoral counseling study program aged 19 -21 years at the Kupang State Christian Institute. The data analysis technique uses simple linear regression analysis. The results of this study prove that there is a positive and significant influence of impulsive behavior on nomophobic tendencies with an F value = 18.782 and a p value = 0.000 at R Square = 0.401. This means that the effective contribution of the impulsive behavior variable to the tendency to nomophobia is 40.1%, meaning that the higher the impulsive behavior, the greater the tendency to nomophobia.